Sizing gold nanoparticles by optical extinction spectroscopy - Scaffardi, Lucía Beatriz (2005)
The measurement of optical extinction is used to determine the size of nearly spherical gold nanoparticles suspended in solution, produced by a 'reverse micelles' process. The contrast between the maximum and the minimum in the extinction spectra around 450 and 520 nm shows a linear dependence with the mean radius of the gold particles less than 3 nm; however, the method can be used to size particles up to 7 nm. Experimental results for extinction spectra can be fitted by Mie's theory if the optical constants from bulk material values are modified by introducing the limitation of the mean free path due to collisions of conduction electrons with the boundary of the nanoparticles.